Implementation of an enhanced recovery after surgery program in the treatment of uterine fibroids with focused ultrasound ablation surgery - Guowei Sang; Xin Zhang; Huamin Fan; Xing Ao; Yushan Chen; Qiuling Shi (International Journal of Hyperthermia)
Background Enhanced recovery after surgery (ERAS) can reduce the length of hospital stay, incidence of surgery-related complications, and postoperative pain. We aimed to demonstrate the implementation of an ERAS pathway in the treatment of uterine fibroids with focused ultrasound ablation surgery (FUAS).Materials and Methods A retrospective data analysis was performed on clinical outcomes encompassing the following three phases: before ERAS (pre-ERAS), during adjustment of ERAS (interim-ERAS), and after the introduction of an ERAS program (post-ERAS). The purpose of describing the interim-ERAS was to provide references for the formulation of the program during the course of FUAS by describing the adjustment processes. Data from patients admitted to the hospital from September 2019 to December 2019 and April 2020 to November 2020 and who met the criteria for FUAS in the treatment of their uterine fibroids were examined. Length of stay, cost of surgery, postoperative pain score, utilization of postoperative analgesics, and incidence of postoperative adverse events were compared across the abovementioned three phases.Results Compared with the pre-phase, the cost of treatment and length of stay were reduced after the implementation of ERAS. The use of analgesics before leaving the operating room, as well as the incidence of postoperative nausea and vomiting, were also reduced.Conclusion The implementation of an ERAS protocol might benefit patients with uterine fibroids treated with FUAS in terms of requiring a shorter hospitalization period, lower costs, and reduced opioid use.